ISLAM DAN DEMOKRASI: HUBUNGAN DAN KOMPATIBILITAS - Fatimah Zuhrah (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2008)
Abstract: Islam and Democracy: Relationship and Compatibilities. In recent years, Islam and democracy have often been characterized as polar opposites. Democracy is seen as modern and forward-looking, whereas Islamic ideas have been portrayed as idealizing a fossilized past and unresponsive to change. This paper presents a discussion of interrelationship between Islam and democracy. Thus it is fair to say that some of the Islamic tenets are in line with the principles of democracy, and perhaps that are potential contradiction of democratic values. Kata Kunci: Islam, demokrasi, politik, Indonesia